Functional validation of target-site resistance mutations against sodium channel blocker insecticides (SCBIs) via molecular modeling and genome engineering in Drosophila. (January 2019) - Samantsidis, George-Rafael; O'Reilly, Andrias O.; Douris, Vassilis; Vontas, John
Abstract: Sodium channel blocker insecticides (SCBIs) like indoxacarb and metaflumizone offer an alternative insecticide resistance management (IRM) strategy against several pests that are resistant to other compounds. However, resistance to SCBIs has been reported in several pests, in most cases implicating metabolic resistance mechanisms, although in certain indoxacarb resistant populations of Plutella xylostella and Tuta absoluta, two mutations in the domain IV S6 segment of the voltage-gated sodium channel, F1845Y and V1848I have been identified, and have been postulated through in vitro electrophysiological studies to contribute to target-site resistance. In order to functionally validate in vivo each mutation in the absence of confounding resistance mechanisms, we have employed a CRISPR/Cas9 strategy to generate strains of Drosophila melanogaster bearing homozygous F1845Y or V1848I mutations in the para (voltage-gated sodium channel) gene. We performed toxicity bioassays of these strains compared to wild-type controls of the same genetic background. Our results indicate both mutations confer moderate resistance to indoxacarb (RR: 6–10.2), and V1848I to metaflumizone (RR: 8.4). However, F1845Y confers very strong resistance to metaflumizone (RR: >3400). Our molecular modeling studies suggest a steric hindrance mechanism may account for the resistance of both V1848I and F1845Y mutations, whereby introducing larger side chains may inhibit metaflumizone binding. Graphical abstract: Image 1 Highlights: Candidate target-site resistance mutations for SCBIs introduced into Drosophila voltage-gated sodium channel by CRISPR/Cas9. In vivo validation confirms association with resistance to indoxacarb and metaflumizone. F1845Y confers very high resistance to metaflumizone. Molecular modeling/docking study indicates steric hindrance inhibits metaflumizone binding.